2010
DOI: 10.1111/j.1365-2362.2010.02318.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammation modulate peroxisome proliferator‐activated receptors with regional discrepancy in diabetic heart

Abstract: Peroxisome proliferator-activated receptor isoforms are differentially expressed in the atria and ventricles. Diabetes can modulate PPARs through increased inflammatory cytokines and oxidative stress, which are attenuated by ascorbate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 40 publications
8
40
0
Order By: Relevance
“…Expression of PPARα may be induced by LXR through the LXRE present in its promoter region [49]. Myocardial expression of PPARα and PPARδ genes is down-regulated in streptozotocin diabetic rats [50][51][52][53] which is in agreement with our observations. Interestingly, in our study administration of TO901317 reversed these changes.…”
Section: Discussionsupporting
confidence: 92%
“…Expression of PPARα may be induced by LXR through the LXRE present in its promoter region [49]. Myocardial expression of PPARα and PPARδ genes is down-regulated in streptozotocin diabetic rats [50][51][52][53] which is in agreement with our observations. Interestingly, in our study administration of TO901317 reversed these changes.…”
Section: Discussionsupporting
confidence: 92%
“…x AE s. n=8, **P<0.01 vs. normal; ## P<0.01 vs. STZ; $ P<0.05 vs. AMG Expression of PPARα is sensitive to oxidant and inflammatory reactions and is modulated by non-PPARα agonists such as antioxidant and anti-inflammatory agents, as we found in the present study. Ascorbic acid has been proved to correct abnormal expression of PPARs toward normal, together with downregulated NADPH oxidase found in diabetic heart (Lee et al 2010). Intervention with berberine relieves renal complications of diabetes by elevating expression of PPARα significantly Noh et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cardiac-restricted overexpression of PPAR-α and PPAR-γ caused deranged myocardial energy metabolism, which contributed to cardiomyopathy [5,6]. Our previous study has also found that DM (diabetes mellitus) can modulate PPARs in cardiomyocytes through increased inflammatory cytokines and oxidative stress [7]. Therefore PPARs play a critical role in the pathogenesis of diabetic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 96%